Reduced Graphene Oxide as a Stabilizing Agent in Perovskite Solar Cells. Issue 22 (29th July 2018) - Milić, Jovana V.; Arora, Neha; Dar, M. Ibrahim; Zakeeruddin, Shaik Mohammed; Grätzel, Michael
Abstract: One of the most challenging obstacles to commercialization of perovskite solar cells (PSCs) is their instability toward environmental conditions. An emerging solution to overcome these challenges relies on graphene‐based composites, in particular, solution‐processable reduced graphene oxide (rGO), whose high electrical and thermal conductivity, along with beneficial passivation effects, display multifaceted utility in PSCs. This review provides a brief summary of functions of rGO in different PSC architectures, from a potential replacement for transparent conductive oxides, through usage in electron‐transporting and perovskite layers, with the particular emphasis on its application as a hole‐transporting material and a spacer layer. Despite ongoing research challenges, the synergy between rGO and PSCs promises to facilitate the future applications of efficient and stable PSCs. Abstract : Reduced graphene oxide has a multidimensional utility in perovskite solar cells, and it is of particular interest in improving their long‐term stability as an alternative hole‐transporting material, passivating agent, and a spacer layer. A brief overview of the present functions and future challenges for the applications of reduced graphene oxide in perovskite solar cells is provided.